Pengaruh Leverage dan Liquidity Terhadap Tax Avoidance Dengan Inventory Intensity Sebagai Variabel Moderasi - David Malindo Pasaribu; Susi Dwi Mulyani (Jurnal Akuntansi, 2019)
This study aims to analyze the effect of leverage and liquidity on tax avoidance with inventory intensity as a moderating variable. The type of data used is secondary data. The sample used is a manufacturing company that is listed active in BEI Period 2015-2017 which can be seen on the official website that www.idx.co.id. Methods of data analysis using is moderated regression analysis (MRA). Data processing is done by using Eviews Version 10 for windows. The results showed that there is a significant negative effect between liquidity with tax avoidance, there is a significant negative influence between inventory intensity with tax avoidance, inventory intensity was able to moderate the effect of liquidity to tax avoidance. In addition, the leverage did not effect to tax avoidance, the inventory intensity was not able to moderate the effect of leverage to tax avoidance. Keywords: Leverage, Liquidity, Tax Avoidance, and Inventory Intensity